Plasmodium telomere maintenance: uncovering the Achilles’ heel for novel antimalarials - Wakai, Theophilus N.; Anzaku, Dorathy O.; Afolabi, Israel S. (Frontiers in Cellular and Infection Microbiology, 2025)
This review examines the potential of disrupting telomere maintenance in Plasmodium as a novel antimalarial strategy. Telomeres are repetitive DNA–protein structures located at chromosome termini, where they preserve genome stability and protect against degradation. Telomere maintenance is crucial for rapid growth, genome integrity, and immune evasion in Plasmodium parasites. Unlike humans, Plasmodium maintains continuous telomerase activity and uses unique telomere-binding proteins across its lifecycle. These features drive parasite virulence and antigenic variation. Emerging evidence suggests that Plasmodium telomeres harbor G-quadruplex (G4) DNA structures, which help stabilize telomeres during replication and may be good targets for small molecules to disrupt their function. Additionally, the parasite depends heavily on its telomerase catalytic subunit, PfTERT, for survival. Inhibiting PfTERT has shown promising results in blocking telomere elongation and impairing replication. Targeting this parasite-specific telomere–telomerase axis may offer a strategic means to destabilize chromosomes, weaken immune evasion, and limit parasite survival, making it a promising antimalarial approach. However, researchers must consider the risks of off-target effects in future drug designs. Though current studies are limited and remain inconclusive, we suggest that future research should investigate combining telomere-directed therapies with existing antimalarials to help overcome resistance and improve treatment outcomes. Herein, we review advances in understanding Plasmodium telomere biology, highlighting its distinct structures, critical telomere-associated proteins, and roles in pathogenesis. We further explore how selective targeting could exploit an Achilles’ heel in parasite survival, offering fresh possibilities for next-generation, parasite-specific malaria therapies.